On the Line Congruences - (:unkn) unknown (My University, 2018)
The purpose of this paper is to find the quantities and surfaces of a line congruence viaexamining it in the dual space and to represent the results more appropriately for computationalapproximations. For this, we take mainly two-dual parameter motion on the dual unit sphere (DUS)so, we get a line congruence corresponding this motion by a new method. Thus, the equations ofthe developable surfaces, the principal surfaces, the focal surfaces and the center surface of the linecongruence are found by coordinate functions. The results are illustrated by examples.
Keywords: Matematik